2017
DOI: 10.1063/1.4980083
|View full text |Cite
|
Sign up to set email alerts
|

Probing the effects of surface hydrophobicity and tether orientation on antibody-antigen binding

Abstract: Antibody microarrays have the potential to revolutionize molecular detection for many applications, but their current use is limited by poor reliability, and efforts to change this have not yielded fruitful results. One difficulty which limits the rational engineering of next-generation devices is that little is known, at the molecular level, about the antibody-antigen binding process near solid surfaces. Atomic-level structural information is scant because typical experimental techniques (X-ray crystallograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…We modified the coarse-grain simulation to include a conjugated PEG chain at a specified site. The methods used are those that have been outlined previously , with a few modifications to include PEG, as detailed in the Methods. While the mechanism behind PEG-based stabilization is not well understood, there are two primary theories: PEG stabilizes proteins through (1) direct interaction with the protein surface ,, or (2) entropic interactions with the solvent. , In this study we limited the simulation to evaluate only the entropic effect.…”
Section: Resultsmentioning
confidence: 99%
“…We modified the coarse-grain simulation to include a conjugated PEG chain at a specified site. The methods used are those that have been outlined previously , with a few modifications to include PEG, as detailed in the Methods. While the mechanism behind PEG-based stabilization is not well understood, there are two primary theories: PEG stabilizes proteins through (1) direct interaction with the protein surface ,, or (2) entropic interactions with the solvent. , In this study we limited the simulation to evaluate only the entropic effect.…”
Section: Resultsmentioning
confidence: 99%
“…This model employed the Karanicolas and Brooks Go-like protein model and a corresponding surface potential that quantitatively describes surface hydrophobicity. Several studies have demonstrated the accuracy of predictions from this model for protein conformation and orientation while interacting with various sensor surfaces. ,,,,, The detailed surface potential and various parameters were developed and published in earlier works , and are included in the Supporting Information for completeness. The simulation details are also described in the Supporting Information.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The model is transferable to peptides of any type and has been used to accurately model proteins of many sizes including enzymes and antibodies. 36,38,39,50 The model was parameterized with data at typical biological conditions (e.g., 6 pH 8, [Na] 200 mM) and is not valid far away from such. However, such limitation is of little importance to this work as antibody arrays are used at biological conditions.…”
Section: A Protein and Modelmentioning
confidence: 99%
“…As has been explained in other works, stabilization on the surface occurs because the protein can make the same favorable contacts in the folded state as in the bulk. 34,37,39,50,60 Specifically, surfaces always stabilize proteins entropically because the surface reduces the entropic cost of folding. [See especially Refs.…”
Section: B Implications For Antibody Arraysmentioning
confidence: 99%